Rendimiento y contenido de antocianinas en respuesta a la modificación de la relación fuente-sumidero en periodo pre y post-antesis en un genotipo local de maíz morado (Zea mays L.), establecido en el sector la Argelia, ciudad de Loja - Maza Poma, Veronica Aracely (2022)
Maize (Zea mays L.) is an important food in the basic food basket, many native varieties have pigmented grain due to the presence of carotenoids or flavonoids of the anthocyanin type (which give the grain its color). Currently, there is an important demand for alternative natural colorants due to the toxicity of synthetic ones, which represents an opportunity for the development of research directed to the use of anthocyanins. The present research was developed with the objective of evaluating the yield and anthocyanin content in purple corn in response to source-sinker modifications in the pre- and post-anthesis period. In the trial, a completely randomized design was established, with 5 treatments and 5 replications; 10 plants were selected in each experimental unit and treatments of 50% defoliation and removal of ears in vegetative and reproductive stages were applied. At the conclusion of the trial, it was established that the treatments with removal of cobs in reproductive stages in purple corn decreased competition between cobs in the plant and showed an increase in yield. Defoliations reduced the leaf area index, however, no statistically significant reductions in aerial dry plant biomass were established, indicating an increase in the radiation use efficiency of the remaining leaves. The effect of the treatments had an influence on the reduction of yield in its components, such as number and weight of grains; however, no influence of these variables was established for anthocyanin content, that is, modifications in source-sinker in corn did not influence the total anthocyanin content in the grain. Keywords: Anthocyanin, purple corn, source-sinker relation.